The Effect of Structured Assignments Assisted by Smartphones in Online Science Learning on Elementary Schools - Debbyanty Debbyanty; Abdullah Sinring; Sandra Sukmaning Adji (PT ARRUS Intelektual Indonesia, 2023)
Learning science has many studies that are abstract and cannot be directly seen. So we need media that can help explain it. In addition to elementary school students who are at the concrete operational stage who are able to think logically but can only understand objects that they can see. The structured assignments method assisted by smartphone media will encourage students to easily understand the material. The research aims to analyze the effect of structured assignments assisted by smartphone in online learning on science learning outcomes for elementary school students. This research with a quantitative approach is an experimental type with a one group pretest-posttest design model that uses class VI students at SD Negeri 102 Makale 5 as research subjects. Based on data analysis using the t test obtained Sig.(2-tailed) 0.00 <0.05, it can be concluded that giving structured assignments assisted by smartphones in online learning has an effect on the science learning outcomes of elementary school students.